A Quality control study on Dermagen Corporation - Dy, Glady; Olvidado, Ingrid O.; Tan, Katheryn C. (Diliman, Quezon City College of Engineering, 2002)
Quality control deals with group of activities designed to ensure adequate quality.This is especially useful for manufacturing products.The group did a quality control study on Dermage Corporation,a pharmaceutical company that manufactures cosmetic products.B.P. Larsen has been experiencing rework problems which reflects the quality of their final products.Although B.P. Larsen does not release products that are less than the acceptable quality level,they incur a lot of costs associated with reworking products to meet final specifications.It was found out that rework was due to incorrect pH value,incorrect viscosity,and incorrect weight.The causes for these problems were identified and analyzed.Control charting was able to confirm that their process is in control.Though in control,their process are incapable as shown in the process capability analysis.Single sampling for their quality points-pH and viscosity-are appropriate.The first problem,incorect pH value,is caused mainly by the workers-when there is incorrect formulation of ingredients.To improve this,the group recommends implementation of SPC (to monitor the process)and developing a reward system for the company,these recommendations are part of the group's general recommendation which apply to all problems identified.The viscosity is a major characteristic for each product.Naturally,incorrect viscosity will demand reworkd and cost.The manufacturing process includes boiling of the oil water bases at separate pots and checking the temperature manually.The group suggest that Dermagen replace this pot by boilers with a built in temperature gauge.Moreover the new boiler must be relocated near the vacuum emulsifying machine which is used for homogenizing the oil water bases.Lastly,for having final products with incorrect weight,Dermagen should purchase an automatic filing machine.This is to replace the method currently used which is manual filing.With this,new machine,Dermagen can utilized as sampling plan instead of 100% inspection.In line with improving quality by solving these problems,Dermagen should develop a quality focus or goal.Their quality goal must reflect the quality that Dermagen imparts in their products the needs and requirements of their customers.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Dermagen Corporation; Pharmaceutical industry; Quality control